Ubiquitylation as a Rheostat for TCR Signaling: From Targeted Approaches Toward Global Profiling - O’Leary, Claire E.; Lewis, Emma L.; Oliver, Paula M. (Frontiers in Immunology, 2015)
Abstract T cell receptor (TCR) signaling must be precisely tuned to limit collateral damage and prevent reactivity to self, while still allowing robust protective immune responses that control pathogen invasion. One process that can be used to promote, modify or terminate TCR signaling is ubiquitylation. During ubiquitylation, ubiquitin is covalently attached to target proteins through a multistep process, in which E3 ubiquitin ligases promote the formation of ubiquitin chains on selected substrates. Ubiquitylation can facilitate protein-protein interactions, direct a protein to a specific subcellular location, or initiate protein destruction. Like phosphorylation, ubiquitylation is a reversible process—deubiquitylating enzymes counter-act ligase function by removing ubiquitin chains. This reversibility also allows for ubiquitin chain “editing.” Based on an emerging wealth of information from genetic loss-of-function studies showing that deregulation of ubiquitylation pathways leads to immune dysfunction, it has become increasingly apparent that the dynamic process of ubiquitylation is critical for normal immune cell function. In this review, we will describe how ubiquitylation acts as a key modulator and integrator of signaling downstream of TCR engagement. Specifically, we highlight the known roles of the substrate-specific E3 ligases and deubiquitylating enzymes in TCR signaling and T cell activation. While it is clear that ubiquitin enzymes tune T cell signaling and T cell function, elucidating the molecular mechanisms by which these proteins modulate T cells has met with significant challenges. Identifying substrates of these enzymes has been a particular challenge, and thus substrates of many E3 ligases and deubiquitylating enzymes remain largely unknown. To that end, we discuss the promise, and some practical considerations, of using proteomics-based techniques for unbiased identification of putative substrates of ubiquitin cascade proteins within primary T cells. These methods provide an exciting opportunity for further defining how TCR signals are regulated and for identifying new targets for therapeutic modulation.